Hypoxia inactivates the VHL tumor suppressor through PIASy-mediated SUMO modification. - Qiliang Cai; Suhbash C Verma; Pankaj Kumar; Michelle Ma; Erle S Robertson (PLoS ONE)
The hypoxic microenvironment contributes to embryonic development and tumor progression through stabilization of the potent transcriptional factor HIFalpha. In normoxia, the tumor suppressor protein VHL acts as an E3 ubiquitin ligase to target HIFalpha for proteolytic destruction. Increasing evidence shows that VHL is a multifunctional adaptor involved in inhibition of HIFalpha-dependent and independent cellular processes. However, the molecular effect of hypoxic stress on VHL functions remains elusive. Here we report that PIASy, a SUMO E3 ligase upregulated in hypoxia, interacts with VHL and induces VHL SUMOylation on lysine residue 171. Moreover, PIASy-mediated SUMO1 modification induces VHL oligomerization and abrogates its inhibitory function on tumor cell growth, migration and clonogenicity. Knockdown of PIASy by small interfering RNA leads to reduction of VHL oligomerization and increases HIF1alpha degradation. These findings reveal a unique molecular strategy for inactivation of VHL under hypoxic stress.